The body in question - Miller, Jonathan (Random House, 1978)
In this original and highly entertaining book, Dr. Jonathan Miller considers the functioning of the body as a subject of private experience. He explores our attitudes towards our bodies, our astonishing ignorance of them, and our inability to read our body's signals. Taking as his starting point the experience of pain, Dr. Miller analyzes the elaborate social process of "falling ill", considers the physical foundations of "dis-ease" and looks at the types of individuals man has historically attributed with the power of healing. His explanations are lucid, wide-ranging and whole-heartedly entertaining.